2015
DOI: 10.1002/cbic.201500087
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐Fed Translation (AFT) Assay: A New High‐Throughput Screening Strategy for Enzymes in Droplets

Abstract: There is an increasing demand for the development of sensitive enzymatic assays compatible with droplet-based microfluidics. Here we describe an original strategy, activity-fed translation (AFT), based on the coupling of enzymatic activity to in vitro translation of a fluorescent protein. We show that methionine release upon the hydrolysis of phenylacetylmethionine by penicillin acylase enabled in vitro expression of green fluorescent protein. An autocatalytic setup where both proteins are expressed makes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…For example, the expression of GFP has been detected inside droplets by single DNA templates [56]. Moreover, when penicillinacylase activity was coupled to the expression of a GFP-reporter, it was also detectable from single gene copies encoding for the acylase enzyme and the GFP [57]. Such fluorescencebased detection of enzymatic activity encoded by single DNA templates is, however, not always possible.…”
Section: Cell-free Expressionmentioning
confidence: 99%
“…For example, the expression of GFP has been detected inside droplets by single DNA templates [56]. Moreover, when penicillinacylase activity was coupled to the expression of a GFP-reporter, it was also detectable from single gene copies encoding for the acylase enzyme and the GFP [57]. Such fluorescencebased detection of enzymatic activity encoded by single DNA templates is, however, not always possible.…”
Section: Cell-free Expressionmentioning
confidence: 99%
“…The use of fluorogenic substrates in enzymatic assays can be problematic in surfactant stabilized emulsions as transport of fluorophores can occur between droplets both in single (Gruner et al, 2019) and double emulsions (Etienne et al, 2018). Woronoff et al (2015) demonstrated an alternative methodology where a proteinogenic amino acid is released after enzymatic turnover and then incorporated in the translation of a reporter protein. Using this approach, they were able to screen for active penicillin acylase enzymes in single gene droplets.…”
Section: Emulsion-based Compartmentsmentioning
confidence: 99%
“…Since DNA molecules distribute into the droplets following Poisson statistics [ 58 , 151 ], limiting dilution produces droplets containing at most one DNA molecule. The small volume of the droplets (femtoliters to picoliters) concentrates expression products to a detectable level [ 52 , 150 , 152 ], but working at the single molecule level may also lead to a significant variance resulting from gene-to-gene expression variation. Nevertheless, this variance can be mostly suppressed by increasing the copy number of gene molecules prior to expressing them [ 152 ].…”
Section: Discovery and Improvement Of Biological Catalystsmentioning
confidence: 99%
“…The small volume of the droplets (femtoliters to picoliters) concentrates expression products to a detectable level [ 52 , 150 , 152 ], but working at the single molecule level may also lead to a significant variance resulting from gene-to-gene expression variation. Nevertheless, this variance can be mostly suppressed by increasing the copy number of gene molecules prior to expressing them [ 152 ]. Clonal population of a DNA molecule can easily be generated in droplets using isothermal [ 58 ] or PCR amplification [ 151 , 153 ].…”
Section: Discovery and Improvement Of Biological Catalystsmentioning
confidence: 99%